PENGARUH STRUKTUR KEPEMILIKAN DAN LABA DENGAN NILAI PERUSAHAANDENGAN KEBIJAKAN DEVIDEN SEBAGAI VARIABEL INTERVENING DI BURSA EFEK INDONESIA TAHUN 2011 - 2013 - Nafiah, Zumrotun (JURNAL STIE SEMARANG, 2016)
This study aimsto investigate themediation effect ofdividend policy in the relationship between ownershipstructure and earning with firm value. Data collection was obtained from manufacturingcompaniesthat listed at IndonesiaStock Exchange. From 56  manufacturing firms which pay dividend, obtained 126companies thatpay dividendsduringthe observationperiodandthentestedwithpathanalysis. The results showedthat the ownership structure had significantlynegativeeffectondividendpolicy, while earningdid noteffect on dividendpolicy. The results also showedthatownership structure does not influence firm value, while earningshave a positiveand significant effect on firm value. Dividend policyis avariable thatmediates relationship between ownershipstructurewith firm value but not mediates relationship between earnings with firm value. The studyconcludedthatinvestorsinIndonesiastill tend to orient to “thebirdinthehandtheory”, investorspreferto invest when dividend was given so it was could effecton the firm value.